The Code of Maya Kings and Queens: Encoding and Markup of Maya Hieroglyphic Writing - Martin de la Iglesia; Franziska Diehr; Uwe Sikora; Sven Gronemeyer; Maximilian Behnert-Brodhun; Christian Prager; Nikolai Grube (Journal of the Text Encoding Initiative)
Maya hieroglyphic script (300 BCE–1500 CE) is a semi-deciphered logographic and syllabic autochthonous writing system from the Americas and is one of the most significant writing traditions of the ancient world. Because of its incomplete state of decipherment, complexity and variation in graphematics, and partially lost lexicon, transliterations cannot be used within the encoding. The project Text Database and Dictionary of Classic Mayan approaches this challenge with an encoding strategy relying on stand-off markup, which is enriched with additional information sources. Using different formats (RDF, XML) and standards (CIDOC CRM, TEI P5), the inscriptions are encoded in a multilevel corpus: (1) a tei_all-compliant schema defining values and rules for the encoding of the text’s topological and structural features, (2) a “Sign Catalogue” for the classification of Maya hieroglyphs, and (3) the tool ALMAH (Annotator for the Linguistic analysis of MAya Hieroglyphs) for linguistic analyses. In this paper, we focus on the TEI schema and highlight our strategy for encoding hieroglyphs without using linguistic transliterations and transcriptions.